INSIDE THE â€œPUZZLEâ€ OF CONTEMPORARY INDONESIAâ€™S REGIONAL AUTONOMY POLICY - Hidayat, Syarif (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
This paper endeavours to see the nature of Indonesian decentralisation and regional autonomy more on the basis of micro level perspective. While most of the previous studies have relied heavily on macro level perspective, such asâ€”assessing how central government has initiated the idea of decentralisation and regional autonomy, investigating the extent to which power has been distributed to the regions, and exploring central governmentâ€™s controls over the regionsâ€”the material presented in this paper has been focussed more on exploring how local state elites themselves have seen decentralisation and regional autonomy. Based on a series of primary data collected in four research locations (the province of West Java, West Sumatra, West Kalimantan, and East Nusa Tenggara/NTT), the author has subsequently ended up with a proposition which says that: the puzzle of contemporary Indonesiaâ€™s regional autonomy policy must be understood on the basis of so called local state elites ambivalence orientation towards decentralisation and regional autonomy policies. The research findings suggested that local state elites had officially manipulated that of ambivalence orientation as the stated justification for their misconduct behaviour in implementing decentralisation and regional autonomy policies. Eventually, the author argues, amongst the distinctive contribution of this paper to the academic development is that it share the work of those who have endeavoured to conceptualise the characteristics of decentralisation and regional autonomy in an epoch the so called â€œtransition towards democracyâ€.